Principal Leadership in Developing the Competence of Islamic Religious Education Teachers - Attok Illah; Rosichin Mansur; Muhammad Fahmi Hidayatullah; Sariman Sariman; Isamaae Seena (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to describe and analyze the leadership of the head of Madrasah Tsanawiyah Al-Ikhlas Bontang in improving the professionalism of Islamic religious education teachers. It uses a descriptive qualitative approach, and data collection techniques are conducted with in-depth interviews, participatory observation, and documentation. The results showed that planning is carried out by collecting ideas through the initial meeting of the year, forming a curriculum development team, obtaining curriculum documents, and determining an assessment program as the basis for implementing evaluations. Furthermore, management implementation through tahfidz learning in local content should be performed every morning for all students with a predetermined schedule. Evaluation through the memorization system positively impacts teachers to form a learning community, and the results of the tahfidz assessment are combined with all groups of Islamic religious subjects.